Comment on On the propagation of errors by Jaskolski (2013). (1st December 2013) - Berman, Helen; Kleywegt, Gerard J.; Nakamura, Haruki; Markley, John L.
<x xml:space="preserve">Abstract</x> The wwPDB responds to the article by Jaskolski [(2013), Acta Cryst. D69, 18651866].